DO OUR LANGUAGES DERIVE FROM BABEL? A BIBLICAL STUDY OF GENESIS 11:1-9 - Melvin Abrillian (Bethel Press, 2024)
This article examines the meanings of Genesis 11:1-9 to straighten out the general Christian understanding that the Tower of Babel story is about the origin of all world languages’ development today. The research method is conducted qualitatively using a narrative hermeneutic approach consisting of background, literary, context, lexical, and grammatical analysis. After analyzing the text, the authors find that Genesis 11:1-9 has historical and theological meaning. Historically, all nations and languages of the Ancient Near East derived from Babel, while theologically, God’s people need to be faithful and obedient to His covenant. Thus, this study concludes that the general Christian understanding is inaccurate because the narrative only talks about the origin of all Ancient Near Eastern languages’ development, not all today’s world languages. Furthermore, the readers also need to understand this story as Moses and the Israelites read it by emphasizing theological, not historical, records.